Ectopic thyroid and Hashimoto’s thyroiditis arising from a thyroglossal duct cyst: a case report - Gök, Üzeyir; Keleş, Erol; Yıldız, Mücahit; Çobanoğlu, Bengü; Dönder, Emir (İstanbul Üniversitesi, 2003)
A seventy-five-year-old male patient presented with a palpable smooth mass that moved upwards on swallowing, extending from the hyoid bone to the cricoid cartilage. Ultrasonography, scintigraphy, and thyroid hormone measurements showed the mass free from the thyroid gland. Following a diagnosis of infected thyroglossal duct cyst by fine needle aspiration biopsy, the mass was removed by surgery.Histopathologic diagnosis was Hashimoto’s thyroidi tis that developed from the ectopic thyroid tissue on the wall of thyroglossal duct cyst.

Yetmiş beş yaşlında erkek hasta, boyun orta hattın- da, hyoid kemiğinden krikoid kartilaja kadar uzanan ve yutkunmakla yukarıya hareket eden kitle flikaye- tiyle baflvurdu. Ultrasanografi, sintigrafi, ve tiroit hormon incelemeleri kitlenin tiroit dokusundan ba- ğımsız olduğunu gösterdi. İnce iğne aspirasyon bi- yopsisi ile enfekte tiroglossal duktus kisti öntanısı kondu ve kitle ameliyatla çıkarıldı. Histopatolojik ta- nı, tiroglossal duktus kisti duvarında ektopik tiroit dokusundan geliflen Hashimoto tiroiditi fleklinde belirlendi.
Tiroglossal duktus kistinde ektopik tiroidit ve Hashimoto tiroiditi: Olgu sunumu